Variation characteristics and the influences of urbanization on hourly intense precipitation before and after monsoon onset over the Pearl River Delta - Tiantong Yang; Xi Lu; Kunlun Xiang; Mingnuo Jiang; Yueping Qiu (Scientific Reports)
Abstract The distinct spatiotemporal characteristics of the hourly intense precipitation (HIP) over the Pearl River Delta (PRD) and the impact of urbanization before and after the monsoon onset from 1972 to 2021 have been investigated using the hourly rain gauge data, nighttime lights data, and land use data. The results show a significant decreasing trend of HIP during the pre-monsoon onset period and a notable increasing trend during the post-monsoon onset period over the past five decades. However, compared to rural areas, rapid urbanization in the PRD after the mid-1990s weakens the HIP reduction, especially in the inland cities of PRD before the onset of the monsoon and enhances the HIP increase, particularly in the southeast inland and west coast cities after the onset of the monsoon. After rapid urbanization, the peak time of HIP has been postponed from 14 LST to 17 LST during the pre-monsoon onset period. HIP tends to occur more frequently in urban areas in the morning (10–12 LST) and evening (19–24 LST) compared to rural areas. In contrast, the impact of urbanization on the diurnal variation of HIP is not obvious during the post-monsoon period, despite higher frequencies of HIP occurring during the daytime (10–15 LST) in the urban areas after rapid urbanization. These findings provide valuable insights for forecasting HIP in urban agglomerations.